Occurrence of Ulva lactuca L. 1753 (Ulvaceae, Chlorophyta) at the Murman Сoast of the Barents Sea. Issue 1 (1st January 2018) - Malavenda, Svetlana; Makarov, Mikhail; Ryzhik, Inna; Mityaev, Maxim; Malavenda, Sergey
ABSTRACT: Findings of Ulva lactuca L. on the Murman Сoast of the Barents Sea are described for the period 2009–2017. This species has not been found in this area for more than 50 years. The occurrence of U. lactuca on the Murman Coast appears to be related to the recent warming of waters in the region.